Production Of Recombinant Urease For Screening Of Helicobacter Pylori Infection - Mohamad, Che Wan Sharifah Robiah (2014)

(untitled)
Helicobacter pylori establishes infection inside human stomach lining and causing duodenal diseases, such as peptic ulcer and potentially into gastric cancer. The invasive diagnostic methods require unpleasant endoscopic procedure for H. pylori detection. Preferably, the noninvasive diagnostic methods would make suspected patients less stressful to procedure for H. pylori detection. The two most preferable noninvasive diagnostic methods are antibody detection (serology) and antigen detection (from fecal) with their own advantages and drawbacks. Helicobacter pylori mempunyai keupayaan untuk menyebabkan jangkitan pada gastrousus dan mengakibatkan penyakit pada pangkal usus seperti radang peptik dan kanser gastrik. Kaedah diagnostik invasif memerlukan prosedur endoskopik yang rumit bagi pengesanan H. pylori. Kaedah diagnostik tidak invasif sebaiknya boleh digunakan untuk mengurangkan tekanan kepada pesakit yang disyaki dijangkiti untuk menjalani prosedur pengesanan H. pylori.